Evaluation of multi-layered graphene nano-platelet composite coatings for corrosion control part I - contact potentials and gas permeability. (15th May 2018) - Richards, C.A.J.; Glover, C.F.; Williams, G.; McMurray, H.N.; Baker, J.
Highlights: Graphene nano-platelets (GNP) impart electrical conductivity to polymer coatings. When GNPs are deposited on metal substrates a contact potential is formed. Additions of GNP reduce oxygen permeation rates of polymer coatings. Abstract: The electronic and diffusion-blocking properties of graphene nano-platelets (GNPs) are quantified with a view to understanding their action as (possible) additives to anti-corrosion coatings. Platelet size and thickness are determined by SEM and BET specific surface area measurements. A Scanning Kelvin probe is used to show that a contact potential of up to 1.2V develops between GNP particles and various metal substrates: silver, copper, iron and zinc. A novel photochemical method is used to show that oxygen permeation rates through a PVB-GNP (polyvinylbutyral) composite coating decrease by over an order of magnitude as GNP volume fraction increases to 0.056.